2022
DOI: 10.5530/ijper.56.2s.100
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Characterisation of Argemone mexicana Leaf Extracts: An Evidence for its Antiandrogenic and Antioxidant Activities

Abstract: Introduction:The naturally available herbs are used for medicinal purpose to promote health. The leaves of Argemone mexicana is one such herb used against different ailments. However, studies involving the characterization of different solvent extracts of the leaves and its antioxidant as well as antiandrogenic properties were limited. Aim: The present study aimed to characterize A. mexicana leaf extracts and determine its biological activities. Materials and Methods: The leaves were washed, shade dried, coars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Quantitative phytochemical analysis of the AM leaves revealed a significant level of antioxidant potential, primarily attributed to the presence of an array of phytoconstituents. As evidence for this, FT-IR analysis showed that there was a broad peak associated with hydroxyl groups in the alcoholic extracts of those AM leaves (54).…”
Section: Antioxidant Activity Of Ammentioning
confidence: 88%
“…Quantitative phytochemical analysis of the AM leaves revealed a significant level of antioxidant potential, primarily attributed to the presence of an array of phytoconstituents. As evidence for this, FT-IR analysis showed that there was a broad peak associated with hydroxyl groups in the alcoholic extracts of those AM leaves (54).…”
Section: Antioxidant Activity Of Ammentioning
confidence: 88%